2014
DOI: 10.3389/fnana.2014.00015
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the human brain: when bigger is better

Abstract: Comparative studies of the brain in mammals suggest that there are general architectural principles governing its growth and evolutionary development. We are beginning to understand the geometric, biophysical and energy constraints that have governed the evolution and functional organization of the brain and its underlying neuronal network. The object of this review is to present current perspectives on primate brain evolution, especially in humans, and to examine some hypothetical organizing principles that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
156
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(172 citation statements)
references
References 113 publications
6
156
0
Order By: Relevance
“…Experiments in which cortical cell number is increased in mice demonstrate that gyrification occurs as cortical surface area increases [100,101]. Gyrification benefits the organism by allowing a larger cortex to fit within the skull, as well as facilitating the formation of local (smallworld) connectivity that is more rapid and energy efficient than long-distance connections [102][103][104]. Parcellation, the subdivision of a brain region into functional and structural subdivisions, would also enable the formation of small world circuitry, and is observed in both mushroom bodies and cortex as they increase in size [58,75,105].…”
Section: Homoplasy Of Morphology and Developmentmentioning
confidence: 99%
“…Experiments in which cortical cell number is increased in mice demonstrate that gyrification occurs as cortical surface area increases [100,101]. Gyrification benefits the organism by allowing a larger cortex to fit within the skull, as well as facilitating the formation of local (smallworld) connectivity that is more rapid and energy efficient than long-distance connections [102][103][104]. Parcellation, the subdivision of a brain region into functional and structural subdivisions, would also enable the formation of small world circuitry, and is observed in both mushroom bodies and cortex as they increase in size [58,75,105].…”
Section: Homoplasy Of Morphology and Developmentmentioning
confidence: 99%
“…Thus, the highest number of cortical neurons (especially those in the frontal lobe), the most efficient connectivity pattern, and consequently, the highest IPC are found in humans. Yet, according to the model developed by Hofman [59], the human brain lies about 20-30% below the optimum, which would be a brain of about 3500 cm 3 . This would be roughly twice the present human brain volume.…”
Section: New Ideasmentioning
confidence: 99%
“…While this number is impressive, even in 2007, humanity's general purpose computers were capable of performing well over 1 x 10 18 instructions per second [5]. Estimates suggest that the storage capacity of an individual human brain is about 10 12 Bytes [28,29]. On a per capita basis, this is matched by current digital storage (5 x 10 21 Bytes per 7.2 x 10 9 people).…”
Section: Digital Storagementioning
confidence: 99%
“…It has been suggested that there are energy and infrastructural constraints that ultimately govern human brain size and activity [85], and that our brain size may be approaching the evolutionary limits of cognitive power [29]. Given that physical restrictions may prevent evolutionary improvements in cognition, the integration of biological with digital processing and information storage is one way forward.…”
Section: Biology and Digital Technology -Cooperation Or Conflict?mentioning
confidence: 99%